Modal Analysis of a Discrete System in the Form of a Rocket Launcher Installed on a Motor Vehicle - Zbigniew DZIOPA; Maciej NYCKOWSKI (Problemy Mechatroniki)
A discrete model of an unguided rocket missile launcher installed on a motor vehicle was developed on the basis of a real assembly. The model is simplified to a vertical plane; it has four degrees of freedom and is adapted for a modal analysis. A mathematical model was derived using the variational method on the basis of the assumed physical model. Analytical dependencies in the form of adjoint second order equations taking ordinary derivatives describe the dynamics of the considered system. The equations describing the autonomous motion of the system provided a definition of the generalized eigenvalue problem and the age equation forming the basis of the characteristic values. An analytical form of particular integrals was assumed for equations describing proper vibrations and the amplitude distribution coefficients were calculated. Four forms of proper vibrations of the considered system were obtained on the basis of the determined eigenvectors.